Korelasi Aktivitas Belajar Siswa di Luar Kelas dengan Evaluasi Hasil Belajar Fikih di Madrasah Tsanawiyah Al-Muttaqin Pekanbaru - Nurhadi, Nurhadi (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2019)
This study stood out of two variables, namely learning activities as X variables (independent / independent variables) and student learning outcomes in Jurisprudence subjects as Y variable (dependent variable). The purpose of this study was to find out the learning activities and student learning outcomes as well as the relationship between learning activities and student learning outcomes in Jurisprudence subjects at the Al-Muttaqin Tsanawiyah Madrasah in Pekanbaru. The subjects of this study were students of the Madrasah Tsanawiyah Al-Muttaqin Pekanbaru. While the object of this research is the correlation of learning activities outside the classroom and evaluation of student learning outcomes on fiqh subjects in the Madrasah Tsanawiyah Al-Muttaqin Pekanbaru. The population of all students amounted to 385 people, with a sample of students of class VII and VIII which numbered 80 people. Data collection uses questionnaires, observation, and documentation. Based on data processing, the results showed that learning activities at the Madrasah Tsanawiyah Al-Muttaqin Pekanbaru were in the "Good" category, and student learning outcomes in the Jurisprudence subjects were in the "Very Good" category. and there is a significant relationship, with the acquisition of a correlation index of 0.733 at a significant level of 5% the table is 0.217% and at the level of significant 1% the table is 0.283%. This means that rch is higher than rtable either at a significant level of 5% or significant 1% (0.217 <0.733> 0.283). From the results of this analysis it can be concluded that Ha is accepted and H0 is rejected. Abstrak Penelitian ini berdiri dari dua variabel, yaitu aktivitas belajar sebagai variabel X (variabel bebas/independen) dan hasil belajar siswa pada mata pelajaran Fikih sebagai variabel Y (variabel terikat/dependen). Tujuan dari penelitian ini adalah untuk mengetahui aktivitas belajar dan hasil belajar siswa serta hubungan aktivitas belajar dengan hasil belajar siswa pada mata pelajaran Fikih di Madrasah Tsanawiyah Al-Muttaqin Pekanbaru. Subjekdari penelitian ini adalah siswa Madrasah Tsanawiyah Al-Muttaqin Pekanbaru. Sedangkan objek penelitian ini adalah korelasi aktivitas belajar diluar kelas dan evaluasi hasil belajar siswa pada mata pelajaran fikih di Madrasah Tsanawiyah Al-Muttaqin Pekanbaru. Populasi seluruh siswa yang berjumlah 385 orang, dengan sampel siswa kelas VII dan VIII yang berjumlah 80 orang. Pengumpulan data menggunakan angket, observasi, dan dokumentasi. Berdasarkan pengolahan data diperoleh hasil bahwa aktivitas belajar di Madrasah Tsanawiyah Al-Muttaqin Pekanbaru berada pada kategori “ Baik”, dan hasil belajar siswa pada mata pelajaran Fikih berada pada kategori “Baik Sekali”. dan terdapat  korelasi yang signifikan, dengan perolehan indeks korelasi 0,733 pada taraf signifikan 5% rtabel adalah 0,217% dan pada taraf signifikan1% rtabel  0,283%. Ini berarti bahwa rch lebih Tinggi dari pada rtabel baik pada taraf signifikan 5% ataupun signifikan1% (0,217 <0,733 >0,283). Dari hasil analisa ini dapatlah diambil kesimpulan bahwa Ha diterimadan H0ditolak. Kata Kunci: Korelasi, Aktivitas, Belajar Siswa, Evaluasi, Hasil Belajar Fikih.